Wanted : talent! Pelliano's quest for A-players - Clety, Victoria Clement de; Stehrer, Katrin; Durlinger, Debbie; Hulsink, Willem (London : Rotterdam School of Management, Erasmus University, 2013)
The Dutch company Pelliano, which was launched in October 2011, aspired to become a worldwide high quality Dutch-Italian fashion label. Pelliano initially started operating as an online business but after a year, the company had already expanded its supply to 120 retailers in 11 countries. Only eight months after the launch they had also expanded their product range, from an exclusive focus on ties to the larger suits business. With an equity capital of ?380.000 and a turnover of ?600.000 in 2012, the company was expecting to reach a capital of ?2.5 million and revenues of ?2 million by 2013. While dealing with fierce competitors, Pelliano firmly believed that its people were making the difference and constituted its greatest competitive advantage, and were the reason for their rapid success.The initial management team, consisting of four young entrepreneurs, was supported by a range of A-player individuals, who were either young and extremely talented, or slightly older yet experienced in fashion.Pelliano had five vacancies for which they sought to find the appropriate A-players as quickly as possible in order to make their growth aspirations come true. By making the use of a wide variety of recruitment methods and offering people good incentives to work for them, the company attracted a huge pool of applicants. However, it was unable to find the right talents for their jobs and fill their positions. How could Pelliano as a growing start-up have been more successful and effective in finding the talent they were looking for?
Originally published in Clement de Clety, V., Stehrer, K., Durlinger, D., & Hulsink, W. (2013). Wanted: Talent!:Pelliano's quest for A-players. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Pelliano; Employees -- Recruiting